Service-oriented middleware for dynamic, real-time management of heterogeneous geosensors in flood management - Assis, Luiz Fernando Ferreira Gomes de (2015)
Natural disasters such as floods, droughts and storms cause many deaths and a great deal of damage worldwide. Recently, several countries have suffered from an the increased number of floods. This has led government agencies to seek to improve flood risk management by providing historical data obtained from stationary sensor networks to help communities that live in hazardous areas. However, the sensor networks can only help to check specific features (e.g. temperature and pressure), and are unable to contribute significantly to supplying the missing information that is required. In addition to stationary sensors, mobile sensors have also been used to monitor floods since they can provide images and reach distances that are not within the coverage of stationary sensors. By combining these heterogeneous sensors, an initiative called Sensor Web Enablement (SWE) seeks to free these applications from the idiosyncrasies that affect the implementation of these heterogeneous sensors. However, SWE cannot always be applied effectively in a context where sensors are embedded and removed dynamically. This dynamic context makes it a complex task to handle, control, access and discover sensors. In view of this, the aim of this work is to dynamically manage heterogeneous sensors involved in flood risk management in near real-time, by enabling interoperable access to their data and using open and reusable components. To achieve this goal, a service-oriented middleware was designed that contains a common protocol message, a dynamic sensor management component and a repository. This approach was evaluated performed by employing an application that prioritizes geographically social media messages based on sensor data.